Transcriptomic analysis of humic acid in relieving the inhibitory effect of high nitrogen on soybean nodulation - Zhang, Wenhua; Li, Jia; Li, Hongya; Zhang, Dongdong; Zhu, Baocheng; Yuan, Hongli; Gao, Tongguo (Frontiers in Plant Science, 2023)
Introduction Nitrogen fertilizer intake promotes soybean growth before the formation of nodules, but excess nitrogen has an inhibitory effect on soybean nodulation. It is important to balance nitrogen levels to meet both growth and nodulation needs. Methods the nitrogen level suitable for soybean growth and nodulation was studied, the role of humic acid (HA) in alleviating the inhibition of high nitrogen on soybean nodulation was analyzed, and transcriptomic analysis was performed to understand its mechanism. Results The results showed that a lower level of nitrogen with 36.4 mg urea per pot could increase the number of nodules of soybean, and a higher level of nitrogen with 145.9 mg urea per pot (U4 group) had the best growth indicators but inhibited nodulation significantly. HA relieved the inhibitory effect at high nitrogen level, and the number of nodules increased by 122.1% when 1.29 g HA was added (H2 group) compared with the U4 group. The transcriptome analysis was subsequently performed on the H2 and U4 groups, showing that there were 2995 differentially expressed genes (DEGs) on the 25th day, accounting for 6.678% of the total annotated genes (44,848) under the test conditions. These DEGs were enriched in mitogen-activated protein kinase signaling pathway-plant, flavonoid biosynthesis, and plant hormone signal transduction based on the –log10 (Padjusted) value in the Kyoto Encyclopedia of Genes and Genomes pathway (KEGG). Discussion HA balanced the nitrogen level through the above pathways in soybean planting to control the number of nodules.